A Family in Iran: Women Teachers, Minority Integration, and Family Networks in the Jewish Schools of the Alliance Israélite Universelle in Iran, 1900–1950. Issue 4 (2nd October 2019) - Headrick, Isabelle S.
ABSTRACT: The Alliance Israélite Universelle, an international Jewish educational philanthropy based in Paris, began to establish modern, secularized schools for girls and boys in North Africa, the Middle East, and Eastern Europe in 1862. The first school was established in Iran in 1898. The Alliance saw itself as addressing the big questions of its time that faced Jews: antisemitism, poverty, and perceived backwardness. It sought to promote the integration of Jews as well as to advance the status of girls through educating them and opposing child marriage. This article examines the integration of Iranian Jews and the professionalization of women in Iran in the first half of the twentieth century, using the Alliance's Jewish female school directors as a case study. It argues that family relationships and networks played a critical role in facilitating both of these modernizing processes.